Efeitos da própolis verde na carcinogênese e angiogênese de tumores de bexiga induzidos pelo bbn em ratas wistar - Dornelas, Conceição Aparecida (2009)
The present study evaluated the effects of prolonged, daily intragastric (ig) or subcutaneous (sc) administration of water-soluble derivative of green propolis extracted in L-lysine and of ig administration of L-lysine upon Wistar rat bladder carcinomas angiogenesis and bladder carcinogenesis induced with BBN (N-butyl-N-[4-hydroxybutyl] nitrosamine). At baseline 125 rats were distributed in 14 groups (I, IIA, IIB, III, IV, V, VI, VII, VIII, IX, X, XI, XII and XIII). Groups I through X received BBN in drinking water for 14 weeks. Group I was treated with propolis ig (150 mg/kg body weight) during 44 weeks beginning 30 days before challenge with BBN. Groups IIA, III and VIII were treated for 40 weeks with propolis (150 mg/kg) sc and ig initiated concurrently with BBN. By the 32nd week, the animals in Groups IV, V, VI, VII and IX were ultrasound-scanned, stratified and reallocated into 4 groups (K, L, M and N) so that the groups contained the same number of animals with small, medium and large tumors or without lesions. Groups L, M and N were treated with L-lysine ig (300mg/kg), celecoxib (30 mg/kg) and propolis (300 mg/kg), respectively, from the 32nd to the 40th week. Groups IIB and K (positive control groups receiving BBN only) were treated with water sc and orally, respectively, during 40 weeks. Groups XI, XII and XIII (negative control groups) received propolis (150mg/kg), L-lysine (150 mg/kg) and water ig, respectively, for 40 weeks. Groups III and VIII were merged into a single group (Group III). The animals were euthanized after 40 weeks. Carcinogenesis was studied in all groups. Angiogenesis was evaluated for Groups K, L, M, N, III and X using quantifying microvascular density of hot spots in histological sections stained with the marker CD-31 and analyzed with specific software. The carcinogenesis index (21.00) and the carcinoma incidence (20%) in Group I (treated with propolis 30 days prior to challenge with BBN) were smaller (p<0.05) than for Group K (control; 39.67 and 66.67%, respectively). The microvascular density of bladder carcinoma hot spots was smaller (p<0.05) for rats treated with propolis for 40 weeks (Group III) and rats treated with propolis from the 32nd to the 40th week (Group N) than for rats receiving BBN only (Group K). Carcinoma multiplicity (p=0.00267), carcinogenesis index (p<0.05) and microvascular density (p<0.05) were greater for Group X (treated with L-lysine) than for group K. In addition, the carcinoma incidence in Group X was 100%, and tumors were more invasive (p=0.0039) than in Group K. The group receiving only L-lysine presented no vesical lesions, indicating that L-lysine in itself does not generate carcinomas. Our review of the literature identified no reports of L-lysine acting as a promoter of bladder carcinogenesis. However, the 100% carcinoma incidence observed in the group treated with L-lysine suggests the amino acid may serve as a model for the study of carcinogenesis. In conclusion, daily ig administration of water-soluble derivative of green propolis at 150 mg/kg body weight reduced the incidence of carcinoma when initiated 30 days prior to challenge with BBN, and inhibited angiogenesis in bladder carcinoma at 150 mg/kg when initiated concurrently with BBN or when administered at 300 mg/kg after 31a week of the initiate BBN.